SAT0193 Low Serum Prealbumin as a Prognostic Factor in Systemic Sclerosis. (23rd January 2014) - Codullo, V.; Cereda, E.; Klersy, C.; Caccialanza, R.; Bonardi, C.; Quarleri, L.; Breda, S.; Caporali, R.; Montecucco, C.
Abstract : Background: Malnutrition is a frequent complication of Systemic Sclerosis (SSc). Its presence is predicted by an active disease (according to Valentini score) and low serum prealbumin levels. Objectives: The aim of the present study is to investigate the prognostic value of this latter serum marker of malnutrition in a cohort of SSc outpatients Methods: Outpatients who satisfied LeRoy's classification criteria for SSc and admitted to a single University Hospital were screened for malnutrition (defined as a body mass index<20 kg/m 2, spontaneous weight loss ≥10% of body weight in the previous 6 months or both) and subsequently followed-up according to EUSTAR recommendations for clinical and instrumental parameters and for survival. The Valentini's disease activity score was calculated at baseline. Presence of other comorbidities (such as diabetes, arterial hypertension, cancer, HCV infection) was also recorded. Statistical analysis was performed with STATA software. Results: Out of 160 patients evaluated at baseline, 158 (20:138 M:F) had complete follow-up data. Mean age was 60.5±11.1 years, diffuse and limited cutaneous patients were 24 and 134 respectively. Main autoantibody reactivities were anticentromere (n=83, 52%) and anti-topoisomerase I (n=29, 18%). An active disease was present in 27 (17%) patients, malnutrition in 24 (15%). Low prealbumin serum concentrations (<20 mg/dl) were detected in 23 (14.5%). Lung involvement (interstitial or vascular) was present in 43 subjects (27%), gastroenteric tract abnormalities in 82 (52%). After a mean follow-up of 3.8 (2.6-4.5) years, 11 (7%) patients had died (9 of SSc-related causes, 2 of cancer complications). Low prealbumin serum levels were significantly associated to a worse survival (univariate HR= 4.89, 1.36-17.56, p=0.015), even when corrected for other significant predictors of mortality in bivariate analyses (lung involvement, g-i involvement, presence of other comorbidities). When evaluated in combination with disease activity, low prealbumin was strongly predictive of survival in patients with an inactive disease (HR=7.3, 1.22-43.64, p=0.03), but not in patients with active disease. In this analysis, presence of malnutrition conferred increased risk of mortality (HR=2.52, 0.65-9.75; p=0.18) although not reaching statistical significance. Conclusions: Low prealbumin values are an important marker of malnutrition in SSc patients and represent a poor prognostic factor in terms of mortality, especially in patients with an inactive disease. Prealbumin levels should be investigated and aimed to be restored to normal in SSc cohorts. Disclosure of Interest: None Declared